Evaluating the Impact of Formative Assessment Intervention and Experiences of the Standard 4 Teachers in Teaching Higher-Order-Thinking Skills in Mathematics - Moyo, Sello Editor; Combrinck, Celeste; Van Staden, Surette (Frontiers in Education, 2022)
Formative assessment may be useful pedagogical practice to enhance the teaching of HOTS in mathematics. This study explored the impact of a formative assessment intervention on (i) students’ achievements in HOTS mathematics tests (pre-and-post) upon their teachers were supported with the instructional intervention, (ii) Standard 4 (Grade 4) teachers’ formative assessment practices. To explore the effects of two-day intervention for professional development teacher training, this study employed mixed methods, sequential embedded approach with single-group, pre-test, intervention (training), post-test instruments. Data were gathered from nine primary schools involving nine teachers and 272 standard 4 students in the Education Southern region in Botswana. Students tests scales were used to measure achievement in mathematical HOTS items along with classroom observations and interviewed the teachers’ experiences and reflections. Data were analysed by logits (theta), descriptive and thematic analysis. The logits analysis showed that students’ achievement in mathematically HOTS items significantly improved from pre-test to post-testing. Post-intervention classroom observation showed that teachers practiced the integration and implementation of some FA strategies. Finally, the teachers’ experience and reflections were found to be favourably inclined to support formative assessment higher-order thinking skills as a strategy to enhance mathematics teaching.